The Influence of Turkish on Cypriot Greek - Ahmet Yıkık (Artuklu Humanities)

(untitled)
When Cyprus was conquered by the Ottomans in 1571, the majority of the local population were Orthodox Greek Christians. After the conquest, Muslim Turks who migrated from Anatolia also settled on the island. Thus, Greeks and Turks, who constituted the two largest communities of the island's population, lived together under Ottoman rule for nearly three centuries. As part of this, the phenomenon of bilingualism was inevitable. Because of inter-community relations, there were interactions between the Turkish and Greek languages spoken on the island. Both communities borrowed words from each other's languages. In the studies conducted to date, the general opinion is that Turkish has not had much influence on the Greek spoken in Cyprus, since the Greeks outnumber the Turks on the island. However, it cannot be said that sufficient studies have been carried out on this subject. The present study focuses on Turkish loanwords in the island's Greek language. Words of Turkish origin, the new forms they have taken, and the words derived from them have been identified. In the light of the findings, and using a sociolinguistic approach, the influence of Turkish on Cypriot Greek is discussed.